RANCANG BANGUN SISTEM INFORMASI GIZI ONLINE PADA RUMAH SAKIT BERBASIS WEB: Sistem Informasi - Octaviani, Vincentia Indri; Sihananto, Andreas Nugroho (Informasi Interaktif : Jurnal Informatika dan Teknologi Informasi, 2022)
In the era of globalization, many activities are carried out online, especially now that the corona virus has spread throughout the world, forcing people to self-isolate at home. This includes, of course, disrupting community activities in conducting health consultation activities. Due to the limitations of these conditions, it is difficult for people to check with nutritionists, which causes people to be less concerned about their nutrition. Therefore, in this journal an Online Nutrition Information System was created. This Information System is one of the projects at PT. Disty Teknologi Indonesia where I am currently participating in the MBKM Internship Stud activity Independent Certified so assigned to work on the project. This Online Nutrition Information System is made in the form of a mobile website that is easy to use anywhere and can be accessed by any device, making it easier for the public to access this website. So, this project is expected to make it easier for the community to conduct nutrition consultations with nutritionists in hospitals. This information system is equipped with several other features besides consultation, which can assist users in their activities other than with a nutritionist. This information system is made using the waterfall method and various plugins/APIs/frameworks such as PHP and Codeigniter to make website performance faster and more efficient. This information system uses MYSQL as a database. This website also uses user security which is quite safe because users can login using a Google+ account that is validated by the Google API. With the login feature using Google, it is hoped that it will make it easier for users and doctors to use this Online Nutrition Information System website.